The Potential of Pequi Oil as a Modulator of Chaperone Expression to Minimize Heat Stress in Laying Hens - Rodrigues, Paola Aparecida Damázio [UNESP]; da Silva, Joyce Andrade [UNESP]; Vieira, José Cavalcante Souza [UNESP]; de Lima, Gabrieli Andressa [UNESP]; Cordeiro, Laís Garcia [UNESP]; Castillo, Elis Omar Figueroa [UNESP]; de Lima Lopes, Júlia [UNESP]; Buzalaf, Marília Afonso Rabelo; de Magalhães Padilha, Pedro [UNESP]; Sartori, José Roberto [UNESP] (MDPI, 2025)
Pequi oil (PO) is a natural feed additive rich in bioactive compounds, which can modulate antioxidant and immunological systems. Thus, the aim of this study was to evaluate the proteomic profile of laying hens supplemented with PO under heat stress conditions. Ninety-six 26-week-old Lohmann White hens were housed in a completely randomized design with a 2 × 2 factorial arrangement, with two climate chambers (cyclic heat stress and thermoneutral) and two diets (control and 0.6% PO). At 38 weeks old, liver samples were collected for protein extraction and digestion, and were submitted to liquid chromatography–tandem mass spectrometry (LC-MS/MS). A total of 996 differentially expressed proteins were identified in the liver proteome of laying hens fed with 0.6% PO under heat stress. These upregulated proteins (0.95 ≤ p ≤ 1.00) are associated with lipid metabolism (apolipoprotein B; vitellogenin-1; ovotransferrin), the antioxidant system (protein disulfide-isomerase A4; superoxide dismutase 1_ soluble; catalase), the immune system (Ig-like domain-containing protein) and chaperones (HSP 90; HSP 70). PO positively modulates a network of heat shock proteins and antioxidant enzymes, and the unique proteins identified can contribute to the discovery of new biomarkers related to heat stress reduction by phytogenic additives.